Physiological and Psychological Mechanisms of Attention-Deficit/Hyperactivity Disorder - Yongmei, Hou (Scientific Research, New Technologies and Applications Vol. 5, 2024)
Background: Physiological mechanisms are the material basis of ADHD and the basis for ADHD drug treatment, and the psychological mechanism is the process of psychological changes that lead to ADHD. Physiological mechanisms interact with physiological mechanisms to jointly determine the development and outcome of ADHD. At present, the physiological and psychological mechanisms of ADHD have attracted increasing attention from the academic community, but there is still no consensus on many issues. Objective: This article aims to provide a basis for the scientific development and implementation of comprehensive intervention measures for ADHD by reviewing the research progress on the physiological and psychological mechanisms of ADHD. Methods: A literature search method was used to organize 46 influential articles, analyze the main physiological and psychological mechanisms of ADHD, explain their principles, functions, and research evidence, and point out the shortcomings of previous research based on this. Results: The onset of ADHD involves various levels and aspects of physiological mechanisms such as changes in genes, blood components, brain structure, and damage to neural function development, as well as the core components of psychological mechanisms - the response inhibition deficiency. Conclusion: Research on the physiological and psychological mechanisms of ADHD is becoming increasingly in-depth, but the application of research methods and techniques needs improvement.